2020
DOI: 10.1021/acsami.0c08241
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Synthesis of Hybrid TiO2-Anisotropic Gold Nanoparticles with Visible and Near-Infrared Activity

Abstract: Anisotropic gold nanoparticles (AuNPs), with their unique physical and optical properties, are emerging as smart and key nanomaterials and are being exploited in many crucial fields. To further improve their range of action, anisotropic AuNPs have been coupled with semiconductors, mainly TiO2 (titania), receiving great interest as powerful platforms both in biomedicine and in catalytic applications. Such hybrid nanoparticles show new properties that arise from the synergic action of the components and rely on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Metal oxide-supported catalyst nanoparticles (MO/C) are one of the most actively pursued catalyst systems for modern chemical applications, including the oxidation of volatile organic compounds, photocatalysis, and energy-harvesting materials [ 1 , 2 , 3 , 4 , 5 , 6 ]. Gold (Au), platinum (Pt), and ruthenium (Ru) nanoparticles (NP) are among the MO/C system types that possess an unexpectedly high catalytic activity, coupled with optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Metal oxide-supported catalyst nanoparticles (MO/C) are one of the most actively pursued catalyst systems for modern chemical applications, including the oxidation of volatile organic compounds, photocatalysis, and energy-harvesting materials [ 1 , 2 , 3 , 4 , 5 , 6 ]. Gold (Au), platinum (Pt), and ruthenium (Ru) nanoparticles (NP) are among the MO/C system types that possess an unexpectedly high catalytic activity, coupled with optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Abalde-Cela et al have shown that gold nanostars can be synthesized in a droplet microfluidics device, where each drop represents a nanoreactor . Very recently, a report by Polito and co-workers has shown that microfluidics devices can not only synthesize gold nanostars with high reproducibility but also can be adapted to coat them with a conformal thin layer of TiO 2 , which opens the door to the opportunity to coat them with a wide range of other metal oxides or semiconducting materials …”
Section: Discussionmentioning
confidence: 99%
“…64 Very recently, a report by Polito and co-workers has shown that microfluidics devices can not only synthesize gold nanostars with high reproducibility but also can be adapted to coat them with a conformal thin layer of TiO 2 , which opens the door to the opportunity to coat them with a wide range of other metal oxides or semiconducting materials. 65 As I have alluded to in passing before, issues in monodispersity and reproducibility drastically affect the plasmonic response of gold nanostars. Differences in spike number, length, morphology, and orientation all affect the position, width, number, and intensity of the LSPR bands.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, given the advantages of excellent mass and heat transfer, precise reaction control and multi‐channel, microfluidic technology has attracted extensive attention in the field of nanomaterial synthesis. [ 56‐60 ] Sugioka and his co‐workers synthesized layered Cu‐Ag nanodots deposited inside the 3D glass microfluidic channel by femtosecond laser direct writing ablation and femtosecond laser selective metallization. [ 57 ] The size and thickness of the decorated Cu‐Ag thin films could be controlled by regulating the laser parameters.…”
Section: Controllable Synthesis Of Silicon‐based Nanohybridsmentioning
confidence: 99%